2009
DOI: 10.1016/j.seizure.2009.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin as adjunctive therapy for partial epilepsy: An audit study in 96 patients from the South East of England

Abstract: Pregabalin seems to be an effective and well-tolerated anti-epileptic drug when used as add-on treatment in patients with refractory partial epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…These rates were not dissimilar to those from other clinical audits where the drug was discontinued by 40-60% of patients over 1-2.5 years (9,(11)(12)(13). These rates were not dissimilar to those from other clinical audits where the drug was discontinued by 40-60% of patients over 1-2.5 years (9,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 41%
“…These rates were not dissimilar to those from other clinical audits where the drug was discontinued by 40-60% of patients over 1-2.5 years (9,(11)(12)(13). These rates were not dissimilar to those from other clinical audits where the drug was discontinued by 40-60% of patients over 1-2.5 years (9,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 41%
“…However, in comparison with TPM, the retention rate appears to be higher with LEV (46 vs. 38% at 2 years), because LEV had a more favorable side‐effect profile than TPM with comparable efficacy (Bootsma et al., 2008b). The results from the available observational studies of PGB and ZNS in patients with refractory epilepsy are also unsatisfactory, with retention rates of 40–60% at 1–2 years for PGB (Carreño et al., 2007; Brandt et al., 2009; Valentin et al., 2009), and 45% and 29% at 2 and 3 years (respectively) for ZNS (Wroe et al., 2008). For both AEDs, treatment discontinuation was mostly because of inefficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, only 4% of patients taking pregabalin reported cognitive problems [Valentin et al 2009]. When present, possible CAEs include deterioration in verbal and visual episodic memory [Ciesielski et al 2006].…”
Section: Pregabalinmentioning
confidence: 99%